Impact of Body Mass Index on In-Hospital Length of Stay after Percutaneous Coronary Interventions - Siddiqui, Mohammad Khalilur Rahman; Rahman, Md Mizanur; Ahmed, Borhanuddin; Molla, Abdul Latif; Uddin, Md Iftekhar; Hossain, Md Belal; Karmaker, Pranob; Ahsan, Mohammad Morshedul (Cardiovascular Journal, 2020)
Background: In-hospital length of stay (LOS) is an important metric for assessing the quality of care and planning capacity within a hospital. Percutaneous Coronary Interventions (PCI) merit short LOS following an uncomplicated procedure. Various factors have been studied that may influence LOS. The relationship between BMI and LOS after PCI has not been thoroughly investigated, especially in Bangladesh. Methods: This cross-sectional observational study was conducted at National Institute of Cardiovascular Diseases, on total 100 patients who underwent PCI with two equally divided groups on the basis of BMI of Asian ethnicity: Group I (BMI < 23 kg/m2) and Group II (BMI e” 23.0 kg/m2). In-hospital outcomes and LOS were observed and recorded after PCI. Results: The mean BMI of study population was 23.9 ± 1.9 kg/m2. The sum of occurrence of adverse in-hospital outcomes was 14.0%. Complications were significantly (p < 0.01) higher in Group I than Group II. Among all adverse in-hospital outcomes, only acute left ventricular failure was found to be statistically significant between groups (p < 0.01). The difference of mean LOS after PCI was higher in Group-I which was statistically significant (p < 0.01). Diabetes mellitus and dyslipidemia were found to be the independent predictors for developing adverse in-hospital outcome (OR= 1.68 and 1.46; 95% CI = 1.25 – 2.24 and 1.16 – 1.83; p = 0.018 and 0.040, respectively). BMI was inversely associated with adverse in-hospital outcome after PCI (OR = 0.95; 95% CI = 0.91 – 0.98; p = 0.007). Conclusion: BMI is inversely associated with adverse in-hospital outcome after PCI. The underweight people are likely to experience longer LOS following PCI. Cardiovasc. j. 2020; 13(1): 19-26